Effect of flavonoids on circulating levels of TNF‐α and IL‐6 in humans: A systematic review and meta‐analysis. Issue 5 (8th March 2013) - Peluso, Ilaria; Raguzzini, Anna; Serafini, Mauro
<x xml:space="preserve">Abstract</x> Epidemiological or in vitro evidence suggests a potential role for flavonoids as anti‐inflammatory agents; we investigated the effect of flavonoids‐rich foods or supplements on tumor necrosis factor‐ alpha (TNF‐α) and interleukin‐6 (IL‐6) in long‐term placebo‐controlled human intervention trials. From 110 human intervention studies selected (MEDLINE, EMBASE, CHORANE, and FSTA databases), 32 long‐term placebo‐controlled trials were suitable for meta‐analysis. After sensitivity analysis, seven studies imputed of bias were excluded and 25 studies were analyzed (TNF‐α, n = 2404; IL‐6, n = 2174). Levels of TNF‐α decreased after flavonoid consumption in the fixed model only (mean difference (MD) (95% CI): −0.098 (−0.188, –0.009), p = 0.032), but metaregression results showed that neither higher dose, nor a longer duration of intervention were associated with a greater effect size. Subgroup analysis did not reveal any significant effect for quercetin and soy, but other sources (red wine, pomegranate, and tea extracts) showed a significant effect size both in fixed (MD (95% CI): TNF‐α −0.449 (−0.619, –0.280), p < 0.001; IL‐6 −0.346 (−0.612, –0.079), p = 0.011) and random (MD (95% CI): TNF‐α −0.783 (−1.476, –0.090), p = 0.027; IL‐6, −0.556 (−1.062, –0.050), p = 0.031) effect models. High‐quality placebo‐controlled trials are needed in order to identify flavonoids as the active ingredients.